Peranan Web Spider Dalam Internet Search Engine - Gozali, Ferrianto; Faezal, Mochamad Fajar (Jurnal Teknik Elektro, 2004)
Information is one of the basic necessities for human being. The complete andtimely information is needed in almost every modern human activities. With internet as aglobal computer network, we can easily retrieve and find a comprehensive information weneed from different places and experts from all over the world. With millions of web sitesalready on the Internet and thousands more being added daily, the chances of someonefinding information they need are very easy and the capabilities of search engines to helpusers in information retrieval are very important.Internet search engine is a software that responsible for spidering and indexingthe information in the Internet and maintaining a database of those information. When akeyword is entered into a search engine, it looks for that keyword in its database anddisplays any relevant records, so it is not really search the global network Internet. Thecapability of Internet Search Engine in information retrieval not only depend on the inputkeyword provided by user but also depend on the capability of the engine to build andmaintain the database due to a dynamic changes of information in the Internet.This paper provides a brief overview about techniques used by internet searchengine especially how it spidering the webs in the internet, indexing the information found inthe web pages and building the database of the information. A model of web spider isdeveloped and tested to show how web spider actually works and to investigate therelationship between the level of spidering with the capability of the search engine. Theperformance of the web spider is tested by spidering Trisakti University Web sitewww.trisakti.ac.id using various key words and level of pages.Keywords: Internet Search Engine, web spider, web site, index, database.